An Analysis of Translation Techniques of Modality in Hortatory Text by English Department Students of UNP - Yogi Ilham; Witri Oktavia (Journal of English Language Teaching, 2020)
This study analyzes the translation technique of modality in hortatory text  and translation accuracy of hortatory text made by the students in academic year 2017 at the English Language and Literature Department. The purpose of this research is to find out the translation techniques used in translation of modality in hortatory text and translation accuracy in translating hortatory text entitled "Defend the forest". This study was descriptive qualitative research used in analysing the technique and the accuracy in translating hortatory exposition text. The instrumentation of this research was translation test. The translating techniques  found were as follows: Established equivalence (86.8%) or 243 data, variation (6.8%) or 19 data, reduction (4.3%) or 12 data, and amplification (2.2%) or 6 data. The results of this study indicate that English Language and Literature Department students use the Established equivalence technique as a technique mostly used to translate hortatory text entitled "defend the forest". For the accuracy in translating hortatory text, the average score is 2,67 that is categorized as an accurate translation.